MODEL PEMBELAJARAN SEUMUR HIDUP BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) UNTUK PEMBERDAYAAN PEREMPUAN PEDESAAN PADA PKBM - anan sutisna (Universitas Sriwijaya, 2020)
Lifelong learning (life long education) has a large role in improving the quality of the human development index. The quality of education in rural communities is far behind and powerless, especially women. Development of the quality of women's education in rural areas needs to be done comprehensively by combining formal, non-formal and informal education. The learning approach used combines andragodi and heutagogi so that lifelong education can be successful. To accelerate the goal of educational development for rural women can be done by forming learning communities through Community Learning Centers (PKBM).Learning for rural women in PKBM needs to be integrated using information and communication technology (ICT) because the community lives in far-off places while learning needs to be done in stages and continuously (life long learning). The use of ICTs in learning for rural women will facilitate the process and interaction in learning. Providing skills and economic empowerment become the main material in learning for rural women. Through education and ICT the empowerment of rural women will be more effective and can improve the quality of life of women socially and economically.